The transformation of urban food systems in Ghana: Findings from inventories of processed products - Andam, Kwaw S.; Tschirley, David; Asante, Seth; Al-Hassan, Ramatu M.; Diao, Xinshen (SAGE Publications, 2018)
Urban food systems in Ghana are changing, along with rapid urbanization and growth in household incomes. Using data from retail inventories of packaged products carried out in eight cities in 2015 and 2016, we find that the interplay of urbanization, imports and domestic processing and packaging has led to some surprising outcomes. Imports are dominant, especially for milled rice and tomato paste, and the shares are higher in smaller cities than in Accra. Imported products are more prevalent in traditional retail outlets than in modern retail outlets. Moreover, imported products come mainly from East Asia; excluding South Africa, which accounts for 6% of imports, less than 3% of imported products were from other African countries.